2001
DOI: 10.1096/fj.00-0527fje
|View full text |Cite
|
Sign up to set email alerts
|

The effect of weightlessness on cytoskeleton architecture and proliferation of human breast cancer cell line MCF-7

Abstract: Because cells are sensitive to mechanical forces, weightlessness might act on stress-dependent cell changes. We hypothesized that the integration of environmental factors might induce specific cytoskeletal architecture patterns, characterized by quantitative image analysis. Human breast cancer cells MCF-7, flown in space in a photon capsule, were fixed after 1.5, 22, and 48 h in orbit. Cells subjected to weightlessness were compared with 1g in-flight and ground controls. Postflight, fluorescent labelings were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
74
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 43 publications
(54 reference statements)
10
74
0
Order By: Relevance
“…Implications of the microgravity experiments and their explanation extend to cell behavior which was seen to be affected by microgravity in another space flight experiment [29]. As recently reported [30], in climbing plants competing for light energy, MTs create a twist obliquely oriented toward the cell's long axis in the root.…”
supporting
confidence: 51%
“…Implications of the microgravity experiments and their explanation extend to cell behavior which was seen to be affected by microgravity in another space flight experiment [29]. As recently reported [30], in climbing plants competing for light energy, MTs create a twist obliquely oriented toward the cell's long axis in the root.…”
supporting
confidence: 51%
“…The morphology of the microtubules in cardiac myocyte cytoskeleton and in MCF-7 cells became diffused under microgravity in space. 23,[35][36] In a microarray based study, it was reported that the expression of cytoskeletal molecules are disturbed, including putative mitochondria-anchoring proteins, A-kinase anchoring protein, and cytoplasmic dynein in space-flown rats. The loss of the cytoskeletal proteins resulted in dislocation of the mitochondria and a postulated leakage of reactive oxygen species from the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…This partial remodeling of the cell cycle was associated with reduced cell proliferation. Prolonged MCF-7 mitosis during MMG is not a new finding and has been attributed to weightlessness-induced alteration of microtubules [4]. Also Meyers et al [11] found that MMG alters proliferation rate, and reported that MMG, by decreasing integrin/MAPK signaling, contributes to reduced osteoblastogenesis during differentiation of human mesenchymal stem cells.…”
Section: Cell Growth and Proliferationmentioning
confidence: 99%
“…Microgravity induces adverse and metabolic effects in animals, humans and cellular systems [1][2][3][4]. We have evaluated the effects of microgravity on cell proliferation, glucose uptake, amino acid uptake and incorporation into proteins in neoplastic human breast cancer cells (MCF-7) and normal murine vascular smooth muscle cells (VSMC).…”
Section: Introductionmentioning
confidence: 99%